EFFECT OF AGE OF SEEDLINGS AND FERTILIZER MANAGEMENT ON YIELD, NUTRIENT CONTENT AND UPTAKE OF RICE (ORYZA SATIVA L.) - P. R. CHAUDHARI; A. P. PATEL,; V. P. PATEL,; L. J. DESAI,; J. V. PATEL,; D. R. CHAUDHARI; D. H. TANDEL (The Bioscan, 2015)
An experiment was conducted under South Gujarat agro climatic condition on clayey soil of the Regional Rice Research Station, Vyara, (Gujarat) during kharif-2012 with a view to study the “Effect of age of seedlings and fertilizer management on yield, nutrient content anduptake of rice (Oryza sativa L.)”.The result revealed that age of seedling and fertilizer treatments significantly influenced the yield and nutrient uptake. The grain and straw yield (4950 and 5598 kg ha-1, respectively) were significantly higher with the19-21 days old seedling (A2) being at par with 12-14 days old seedling (A1). Significantly lower grain and straw yield of rice recorded under A3 (25-28 days old seedling).Thegrain and straw yield (4928 and 5514 kg ha-1, respectively) were significantly higher due to fertilizers treatment under the application ofurea briquettes + 20 per cent N through urea (F3) which was remained at par with treatment urea briquettes (F1) and whiletreatment recommended dose of fertilizers(F2) was found inferior.N, P and K content and uptake in grain and straw recorded significantly higher under 19-21 days old seedling remained at par with 12-14 days old seedling.